في مهارة الاستماع لدى طلاب الفصل الثامن في مدرسة التريبة الإسلامية جندونج آغم "Animasi" تأثير استخدام وسيلة الرسوم المتحركة - Azia, Nurul; Arsya, Fajriyani (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2024)
This research aims to determine the effect of using animation media in Arabic language learning to improve students' listening skills at Madrasah Tarbiyah Islamiyah Candung Agam. This research uses a qualitative approach with experimental methods. Data collection techniques through test questions. A qualitative approach was chosen to provide an in-depth understanding of the experiences and views of teachers and students regarding the application of animated learning media. This research involved several steps. First, through the observation stage, the researcher actively observed and recorded how animation media was applied in Arabic language learning at the Candung Agam Islamic Tarbiyah Madrasah. and Interaction between teachers and students as well as students' responses to this learning media are the main focus of observation. Second, test questions were carried out on students to determine the extent of their improvement and understanding regarding the use of animation media. Based on data analysis, this research concludes that the use of animation-based learning media provides significant benefits in improving students' Arabic listening skills at Madrasah Tarbiyah Islamiyah Canduang Agam.  Through this learning media, teachers can present learning material in a more interesting and interactive way, which directly attracts students' interest and attention. Apart from that, the use of animation media also increases students' motivation in learning and listening to Arabic.